National goals of sustainable development (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article explores the regional dimension of sustainable development in Uzbekistan, focusing on key strategies and initiatives aimed at fostering economic stability, social equity, and environmental preservation at the local level. By examining the unique challenges and opportunities faced by different regions within Uzbekistan, this article underscores the importance of tailored policies and targeted investments to address regional disparities and promote inclusive development. Through a comprehensive analysis, it highlights the pivotal role of regional economies in achieving the overarching objectives of sustainable development, thereby contributing to the prosperity and well-being of Uzbekistan's diverse communities.